Breaking the addiction to process : an introduction to agile project management. - Scanlon-Thomas, Elizabeth (IT Governance Pub., 2011)
Companies using traditional development methods are finding it increasingly difficult to maintain profitable business relationships in today's climate. Agile is a flexible, adaptable system and this book will help you implement it for maximum impact and success for your business. With Agile you can deliver the results your clients want, with the results you want too!